Seizure localization using ictal phase-locked high gamma. (9th June 2015) - Weiss, Shennan A.; Lemesiou, Athena; Connors, Robert; Banks, Garrett P.; McKhann, Guy M.; Goodman, Robert R.; Zhao, Binsheng; Filippi, Christopher G.; Nowell, Mark; Rodionov, Roman; Diehl, Beate; McEvoy, Andrew W.; et al.
<x xml:space="preserve">Abstract</x> Objective: To determine whether resection of areas with evidence of intense, synchronized neural firing during seizures is an accurate indicator of postoperative outcome. Methods: Channels meeting phase-locked high gamma (PLHG) criteria were identified retrospectively from intracranial EEG recordings (102 seizures, 46 implantations, 45 patients). Extent of removal of both the seizure onset zone (SOZ) and PLHG was correlated with seizure outcome, classified as good (Engel class I or II, n = 32) or poor (Engel class III or IV, n = 13). Results: Patients with good outcomes had significantly greater proportions of both SOZ and the first 4 (early) PLHG sites resected. Improved outcome classification was noted with early PLHG, as measured by the area under the receiver operating characteristic curves (PLHG 0.79, SOZ 0.68) and by odds ratios for resections including at least 75% of sites identified by each measure (PLHG 9.7 [95% CI: 2.3–41.5], SOZ 5.3 [95% CI: 1.2–23.3]). Among patients with resection of at least 75% of the SOZ, 78% (n = 30) had good outcomes, increasing to 91% when the resection also included at least 75% of early PLHG sites (n = 22). Conclusions: This study demonstrates the localizing value of early PLHG, which is comparable to that provided by the SOZ. Incorporation of PLHG into the clinical evaluation may improve surgical efficacy and help to focus resections on the most critical areas.